Optimizing Rehabilitation: The Potential to Assess Cardiorespiratory, Neuromuscular and Biomechanical Adaptations to Exercise of Children with Cerebral Palsy in the Face of Intra-Individual Variation - Angeline N Leunkeu; Roy J Shephard; Said Ahmaidi (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2017)
The aim of this article is to assess the practical clinical value of measures used to examine physiological (cardiorespiratory and neuromuscular) and biomechanical (spatio-temporal and baropodometric) responses to effort in children with cerebral palsy (CP). Cardiorespiratory data included a 6 minute walking test and cycle ergometric determinations of peak respiratory gas exchange V( O2peak,VE,) by Cosmed K4b2 gas analyzer. Peak isometric strength and fatigue for the quadriceps muscle were tested on the Cybex (Norm II) isokinetic apparatus, noting the time required for effort to decrease to 50% of the maximal voluntary isometric force (MVIF). Qualitative analysis of the associated electromyographic signal examined the root mean square voltage and median frequency. Biomechanical data included gait cycle characteristics (speed, step length, step frequency, impulse, time of contact, step duration, time of double support) and plantar pressure peaks measured at a total of 8 sites. Values for all of these variables met or exceeded conventional standards of reliability and validity, but a substantial intra-individual test-retest variation limited the potential to interpret changes in an individual's physical condition. The authors emphasize that whether looking at aerobic function, muscular fatigue or gait, it is necessary to gauge the effectiveness of training programmes in terms of grouped rather than individual responses.